KONSEPSI NATAH DAN LEBUH SEBAGAI â€œRUANG KESEIMBANGANâ€ DALAM ARSITEKTUR TRADISIONAL BALI - Wijaya, I Kadek Merta (Jurnal Arsitektur ZONASI, 2019)
Natah and lebuh are interpreted as empty outer space in spatial planning of traditional Balinese settlements. In traditional Bali settlements in mountain areas, natah in the form of elongated empty space that binds or becomes the orientation of the times buildings, while traditional Bali settlements in lowland areas in the form of empty space as a center centered orientation of the building configuration. Lebuh is a space that is is in the outermost part of a residential yard or on a scale the settlements are in the village border in the direction of the teben orientation. Natah space and lebuh usually used as a ceremonial space for renewal (a ritual to neutralize power negative), a wide ritual of banten (giving the ceremony facilities that have been used in front under the entrance), downstreaming the process of ritual activities in a home yard and the village environment, as a space for social activities and local customs. Aim this study is an interpretation of the conception of the balance of the natah space and lebuh on traditional Balinese settlements of residential and residential scale using qualitative interpretative exploratory methods through a system of social activity approaches, rituals and safety evacuation and local and general concepts about the dichotomy of space. The results of the research obtained are the natah space and the lebuh as a empty space outside and being in the orientation of nista or teben containing ritual, social and conception safety seen from the spatial layout and function of the two spaces.